2003
DOI: 10.1007/s00299-003-0653-2
|View full text |Cite
|
Sign up to set email alerts
|

Genome size and base composition of five Pinus species from the Balkan region

Abstract: The 2C DNA content and base composition of five Pinus (2 n=24) species and two Pinus subspecies from the Balkan region have been estimated by flow cytometry. P. heldreichii (five populations) and P. peuce (one population) were assessed for the first time, as also were subspecies of P. nigra (three populations-two of subspecies nigra and one of subspecies dalmatica) along with P. sylvestris, and P. mugo from the same region. The 2C DNA values of these Pinus ranged from 42.5 pg to 54.9 pg (41.7-53.8 x 10(9)bp), … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
32
0
1

Year Published

2006
2006
2018
2018

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(35 citation statements)
references
References 25 publications
2
32
0
1
Order By: Relevance
“…Chromosome lengths (12.79-7.55 µm), much lower than those observed in P. heldreichii (14.93-8.94 µm), reflect also obvious differences in genome size which was 45.5 pg and 50.01 pg respectively (Tab. IV) [2]. Values of r and AsI (%) for both species are in concordance with the results obtained by other authors [4,21,43] which emphasizes karyotype uniformity found by conventional cytogenetical techniques.…”
Section: Discussionsupporting
confidence: 81%
See 1 more Smart Citation
“…Chromosome lengths (12.79-7.55 µm), much lower than those observed in P. heldreichii (14.93-8.94 µm), reflect also obvious differences in genome size which was 45.5 pg and 50.01 pg respectively (Tab. IV) [2]. Values of r and AsI (%) for both species are in concordance with the results obtained by other authors [4,21,43] which emphasizes karyotype uniformity found by conventional cytogenetical techniques.…”
Section: Discussionsupporting
confidence: 81%
“…Recently employed techniques of fluorescent in situ hybridization (FISH) revealed organization of ribosomal genes in Pinus species [9,26,28,34]. Last decade was particularly marked by genome size investigations of Pinus species [2,20,29,39,40,48,50]. All these methods are very useful for consideration of phylogenetic and systematic relationships among pine species.…”
Section: Introductionmentioning
confidence: 99%
“…Variations in genome size between closely related species may reflect adaptive and evolutionary differences at the nuclear level (Ohri, 1998). This phenomenon was particularly obvious for Pinus, a genus with a broad distribution (Bogunic et al, 2003). These variations may derive from retroelements, primarily the LTR (long terminal repeat) retrotransposons (Vicient et al, 1999) and other repetitive DNA content (Flavell et al, 1974 Brought to you by | MIT Libraries Authenticated Download Date | 5/9/18 9:24 AM in DNA content through selective removal or increase of small amounts of DNA contribute greatly to interspecific differentiation (Ohri and Khoshoo, 1986;Wakamiya et al, 1993;Jeffrey et al, 2005).…”
Section: Discussionmentioning
confidence: 99%
“…The relationship of DAPI and PI with base composition was described by Godelle et al (1993), as follows: The nine A. ramosa and the seven C. billbergioides individuals showed the same mean 2C DNA content and base composition in that R is the ratio between fluorescence intensity of the peak corresponding to Bromeliaceae and that of S. lycopersicum, and r = 3 for DAPI (Meister and Barow 2007). The proportion of GC bases was calculated as suggested by Bogunic et al (2003): GC (%) = 100%-AT%.…”
Section: Base Compositionmentioning
confidence: 99%